Strategi Pemasaran Produk Sabun Berbahan Dasar Limbah Minyak untuk Meningkatkan Penjualan - Fredy Kurnia Sandy; Peny Septiani Suranto; Radyta Alicia Pramestia Sigit; Muhammad Irfan; Umi Nuraini (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2024)
Wadas Village has a Waste Bank which functions to process or recycle waste so that it becomes usable products. Dahlia Paud, which is a unit of the Karawang Main Waste Bank, has a lot of potential for small businesses made from waste. One of them is mijel soap made from used cooking oil, developed by women in Wadas Village. However, this business is still managed traditionally and has not been optimized through the use of information technology such as the internet to market products. In general, this paper analyzes the obstacles, and advantages found in product and product marketing. This community service aims to introduce mijel (used cooking oil) soap products so that they can be known by the wider community and help increase sales.